Sovereignty, Protection and the Limits to Regional Refugee Status Determination Arrangements - Dehm, Sara (Utrecht Journal of International and European Law, 2012)
This case note explores the recent Australian High Court decision of Plaintiff M70/2011 v Minister for Immigration and Citizenship, which declared a proposed regional refugee status determination arrangement between Australia and Malaysia to be unlawful under Australian law. While the decision was determined by the specific statutory construction of Australian's migration legislation, it nonetheless draws attention to the legal character of what constitutes 'protection' under international refugee law and suggests the necessary legal and factual conditions that must exist in a 'third country' in order for any transfer of refugee processing and recognition procedures to be seen to satisfy Convention obligations. It thus represents a significant judicial challenge to the contemporary trend pursued by wealthy industrialised nations in the Global North towards erecting barriers for accessing domestic asylum regimes and adopting policies that in effect outsource and extraterritorialise asylum processing under the guise of 'burden sharing' or regional 'harmonisation'. This case note reads the decision as a particular re-articulation of sovereign authority, borders, belonging and place-making.